Activation of the Fibrinolytic Enzyme System in Laboratory Animals and in Man - Baillie, A. J; Sim, A. K (Thrombosis and Haemostasis, 1971)
The activation characteristics of the fibrinolytic system of several species have been evaluated in vitro and compared with the human enzyme system. The cat, dog and baboon would appear to be the most suitable species for further study of fibrinolytic activation. The present findings have been found to parallel the species differences in platelet behaviour which have been reported separately from this laboratory.